THE CONSTRUCTION OF SOFT SETS FROM FUZZY SUBSETS - Hijriati, Na'imah; Yulianti, Irma Sari; Susanti, Dewi Sri; Anggraini, Dewi (PATTIMURA UNIVERSITY, 2023)
Molodtsov introduced the concept of soft sets formed from fuzzy subsets in 1999. The soft set formed from a fuzzy subset is a particular form of a soft set on its parameter set. On a soft set formed from a fuzzy subset, the parameter used is the image of a fuzzy subset which is then mapped to the collection of all subsets of a universal set. This research explains the construction of soft sets formed from fuzzy subsets. We provide the sufficient condition that a soft set formed from a fuzzy subset is a subset of another soft set. Also, give some properties of the soft sets formed from a fuzzy subset related to complement and operations concepts in soft sets